The Implications of Performance in the Teaching of Poetry at Rufus Giwa Polytechnic, Owo, Nigeria - Akinkurolere, Susan.O.; Adewumi, Samuel; Aminu, Segun; Olowu, Ayodeji; Adetoro, Abiodun (Annals of Language and Literature, 2021)
There is no doubt, the importance of the literary aspect of English Language, as stipulated in the National Board for Technical Education(N.B.T.E) Curricula for students at National Diploma and Higher National Diploma levels in the polytechnics, can never be over emphasized. The curricula are designed in such a way that students study the three genres of literature before graduating with Higher National Diploma. Poetry, a more advanced, abstract and complex genre of literature, is taught at HND level and students are less interested as there are no explicit characters or actors. Hence, this study examined the implications of performance in the teaching of poetry and assessed the performances of HND students at Rufus Giwa Polytechnic Owo in order to demonstrate the viability of the approach. The study adopted the theoretical framework of situation cognition theory, through which, students’ emotions were linked to learning in the course of demonstrating real life situations. The intervention was administered on five hundred students and the best one hundred scores on the basis of twenty-five scores from each faculty were selected and analysed. There was a significant increase in the previous mean score of 5.94 to 9.05. Hence, students had a better understanding of poetry and lecturers, also, had the opportunity a more defined method of making poetry an adventurous experience in the classroom, especially, for the students. Therefore, engaging students in the performance of study poems is recommending for students of tertiary institutions.
Keywords: Poetry; Teaching; Performance